Pengaruh Rekrutmen, Latar Belakang Pendidikan Dan Seleksi Terhadap Kinerja Karyawan (Study Pada Karyawan KUD Pakis Malang) - Ari firmansyah; Muhammad Agus Salim; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine the effect of Recruitment, Educational Background and Selection on Employee Performance Study on KUD Pakis Malang employees. The type of research used is quantitative research with questionnaire distribution method. The sample in this study were 33 respondents and data processing using the SPSS computer program. This study has met the requirements of validity and reliability. The data analysis used in this study is the classical assumption test, multiple linear regression, hypothesis testing and coefficient of determination analysis. The variables used in this study are the performance variable (the dependent variable), while the independent variables are Recruitment, Education Background, and Selection of Employee performance. The results of this study conclude that the variables of recruitment, educational background and selection have an effect both simultaneously and partially on employee performance. Keywords: Employee Performance, Recruitment, Educational Background, and Selection.